An empirical study of trade in goods between China and Brazil: Analysis of competitiveness and complementarity - Shuhao Zhao; Tianao Chang; Yumo Ni; Ping Zhou (Economies, 2023)
China and Brazil established the 'Comprehensive Strategic Partnership' in 2012. Since the establishment of the partnership, China and Brazil have continued to deepen economic and trade cooperation, and cooperation in various fields has achieved remarkable results. China has long been consistent in maintaining its status as Brazil's largest export destination and source of imports. The total volume of bilateral trade between China and Brazil has significantly increased, and the trade structure in goods is becoming increasingly diversified. The total volume of bilateral trade between China and Brazil has grown considerably, and the trade structure in goods has become increasingly diversified. On 20 April 2023, when Brazilian President Lula visited China, China and Brazil issued a joint statement on deepening the 'Comprehensive Strategic Partnership', further deepening the cooperation in trade in goods has become a consensus. From the perspective of goods trade under the comprehensive strategic partnership, the article analyses the complementarities and competitiveness of goods trade between China and Brazil with the help of relevant formulas to form a complete and transparent study of the goods trade between the two countries.
Keywords: 330